Optimized Synthesis of Lipase-Catalyzed 3-O-(3',3'-Dimethylsuccinyl)-Betulinic Acid by Immobilised Novozyme 435 - Gunong @ Mohd Shah, Siti Aminah (2010)
The derivative of betulinic acid, 3-O-(3',3'-dimethylsuccinyl)-betulinic acid (5) was successfully synthesized by the reaction of betulinic acid and 2,2-dimethylsuccinic anhydride, catalyzed by immobilized lipase from Candida antartica (Novozyme 435) in chloroform. The structure of the product was determined by spectroscopic methods. Effects of different reaction parameters were investigated and optimized in the model reaction. Optimum conditions to produce 3-O-(3',3'-dimethylsuccinyl)-betulinic acid (5) up to 78.1 % were observed at reaction time; 24 h, amount of enzyme; 100 mg, betulinic acid (1) (0.055 mmole) to 2,2-dimethylsuccinic anhydride (0.055 mmole) substrate molar ratio; 1:1 at 50 °C. Response surface methodology (RSM) based on a five-level, three variables and central composite rotatable design (CCRD) was employed to evaluate the interactive effects of the parameters used in the synthesis methodology such as reaction time, temperature and enzyme amount. It was observed that, simultaneous increase in reaction time, temperature and amount of enzyme will increase the yields of 3-O-(3',3'-dimethylsuccinyl)-betulinic acid (5). Based on the analysis of ridge max, the optimum conditions for the synthesis of 3-O-(3',3'-dimethylsuccinyl)-betulinic acid (5) were as follows: 53.6 °C of reaction temperature, 28.15 hours of reaction time and 122 mg of enzyme for 1.0 mmol of betulinic acid (1) and 1.0 mmol of 2,2-dimethylsuccinic anhydride. The optimum predicted for percentage yield was at 83.93 % in which agree well with the actual value of 84.38 %. In brief, the anticancer activity of betulinic acid (1) and 3-O-(3',3'-dimethylsuccinyl)-betulinic acid (5) were evaluated against cultured human T-promyelocytic leukemia (HL-60), human breast cancer (MCF-7), human cervical carcinoma cancer (HeLa) and mouse embryonic fibroblast normal cell line (3T3) cells lines. In particular, 3-O-(3',3'-dimethylsuccinyl)-betulinic acid showed nontoxic activity against human T-promyeloctic leukemia (HL-60) and human breast cancer (MCF-7) with IC50 > 30 μg/ml. However, it has better activity against human cervical carcinoma cancer (HeLa) (IC50 1.9 μg/ml) compared to betulinic acid (IC50 4.8 μg/ml). Interestingly, both compound were highly inactive against mouse embryonic fibroblast normal cell line (3T3) with IC50 > 30 μg/ml.